2022
DOI: 10.1002/jrs.6419
|View full text |Cite
|
Sign up to set email alerts
|

Water in ionic liquids: Raman spectroscopic studies

Abstract: The application of Raman spectroscopy in studies of ionic liquid (IL) systems having water is presented here. The presence of water can be intentional or unintentional. Since water severely affects IL's physical and chemical properties, it is very important not only to identify but also to understand the role of water. It will be evident from this short review that Raman spectroscopy has immensely helped to understand the IL/water mixture at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…As the water content increases, the Raman shift at the O−C−O peak attains a saturation value, reflecting the predominance of the anion− water interactions. The water−IL transition is reflected by the binding of the IL anions with water molecules, whose size is smaller than the ionic liquid cations, therefore resulting in a Raman shift that translates toward smaller length scales (or higher wave numbers, as can be seen in Figure 5C), as also described by Saha et al 35 Analogously, Shi and coauthors 62 investigated water−EMImAc interactions, finding that, at low water content (1 wt %), the acetate anions are only coordinated by 0.25 water molecules, whereas at W c = 5 wt % water, each acetate anion is coordinated by two water molecules. At higher water concentrations (W c > 7 wt %), authors found that water− anion interactions predominate over the water−water and the water−cation ones.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…As the water content increases, the Raman shift at the O−C−O peak attains a saturation value, reflecting the predominance of the anion− water interactions. The water−IL transition is reflected by the binding of the IL anions with water molecules, whose size is smaller than the ionic liquid cations, therefore resulting in a Raman shift that translates toward smaller length scales (or higher wave numbers, as can be seen in Figure 5C), as also described by Saha et al 35 Analogously, Shi and coauthors 62 investigated water−EMImAc interactions, finding that, at low water content (1 wt %), the acetate anions are only coordinated by 0.25 water molecules, whereas at W c = 5 wt % water, each acetate anion is coordinated by two water molecules. At higher water concentrations (W c > 7 wt %), authors found that water− anion interactions predominate over the water−water and the water−cation ones.…”
supporting
confidence: 61%
“…Over the years, several authors have reported about cellulose/EMImAc/water interactions and, in particular, the sol–gel transition of cellulose/IL solutions driven by water absorption. This phenomenon has also been exploited to regenerate cellulose. , A proposed mechanism for the sol–gel transition is based on the water–ionic liquid and cellulose–ionic liquid hydrogen bonding competition . As water is added into the solution, strong binding between water molecules and the acetate anions occurs . The ion–pair and polymer chain–ionic liquid interactions are disrupted by the presence of water molecules, freeing the hydroxyl groups of the polymer chains, which in turn drive intercellulose hydrogen bonds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the low-frequency region, the Raman spectra of PAW generated with the hybrid system display peaks of greater intensity than those generated with GAPJ and DBD, indicating that the hybrid system may induce changes in the intermolecular modes of water. Given water's complex tetrahedral molecular structure [71], the relative intensity of the vibrational modes are influenced by the presence of ions [72]. For instance, Cammarata et al reported that the strength of hydrogen bonding between water molecules and ions depends on the enthalpy changes associated with hydrogen bonding (∆H) [73].…”
Section: Vibrational Properties Of Pawmentioning
confidence: 99%
“…Raj et al [ 8 ] investigated tetrahydrofuran‐water binary solutions using the cutting‐edge Raman MCR technique. Saha et al [ 9 ] reviewed Raman spectroscopic studies of water in ionic liquids, focusing on interaction between water and ionic species at the molecular level. Choe et al [ 10 ] applied Raman MCR microscopy to human skin for in vivo quantification of water.…”
mentioning
confidence: 99%